The Everything Box: The Wrong Dead Guy - Book 2 - Kadrey, Richard (New York, NY : Harper Voyager, an imprint of HarperCollinsPublishers, 2017)
Coop, a master thief sort of gone legit, saved the world from an ancient doomsday device--heroism that earned him a gig working for the Department of Peculiar Science, a fearsome top secret government agency that polices the odd and strange. Now Woolrich, Coops boss at the DOPS, has Coop breaking into a traveling antiquities show to steal a sarcophagus containing the mummy of a powerful Egyptian wizard named Harkhuf. With the help of his pals Morty, Giselle, and a professor thats half-cat, half-robotic octopus, Coop pulls off the heist without a hitch. Its not Coops fault that when DOPS opened the sarcophagus they didnt find the mummy they were expecting. Well, it was the right mummy, but it wasnt exactly dead--and now its escaped, using a type of magic the organization hasnt encountered before. Being a boss, Woolrich blames his underling for the screw up and wants Coop to find the missing Harkhuf and make it right, pronto. Digging into Harkhufs history, Coop thinks the mummy is hunting for an ancient magical manuscript that will help him bring his old lover back to life. Which wouldnt be so bad if she wasnt a warrior sorceress hell-bent on conquering the world with her undead armies. Coop would very much like to run from the oncoming chaos. Its one thing to steal a mummy, but another to have to deal with head-hunting bureaucrats, down-on-their luck fortune tellers, undead mailroom clerks, and a rather unimpressed elephant. Unfortunately, theres nowhere to run. If he wants the madness to stop, hes going to have to suck it up and play hero one more time. But if Coop manages to save the world AGAIN, hes definitely going to want a lot of answers. And a raise.
Keywords: Mummies -- Fiction; Thieves -- Fiction; Paranormal fiction